Effect of treated and untreated filler loading on the mechanical, morphological, and water absorbent properties of water hyacinth fibers-low density polyethylene composites - Supri, Abd Ghani, Dr.; Lim, B. Y. (Penerbit Universiti Sains Malaysia (USM), 2011)
Link to publisher's homepage at http://www.usm.my/